Giving or not giving? Experienced EFL university teachers’ beliefs and rationales of written feedback - Murtiningsih, Sri Rejeki; Sumantri, Agus; Hidayatulloh, Sibakhul Milad Malik (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This current research aims to investigate the beliefs and rationales of EFL university teachers about giving or not giving written feedback to their students. The researchers employed a descriptive qualitative approach in the execution of this study. Three experienced EFL university teachers agreed to participate in in-depth interviews to gain the data. This research revealed five distinct beliefs regarding providing written feedback. They hold beliefs about giving feedback based on the importance of giving feedback, the role of giving feedback to other types of feedback, the length of feedback, students' competence-based in giving feedback, and the importance of giving balanced feedback. As for their rationales for giving and not-giving feedback, several findings were documented. They provided written feedback because it gave some crucial information by showing students' identifiable learning records and enhancing their academic output. Also, it holds relevance to the teachers’ teaching profession. On the other hand, their rationale for not-giving written feedback could be noticed as written feedback, to some extent, demotivated students and took much more time to provide feedback. In the end, teachers' pedagogical implications are also presented by recalling the findings of this current research.